(untitled) (Dissertare, 2022)
Within the theme of the modification of communal regulatory plans in Chile, some columns that are usually exposed to public discussion are Providencia, Santiago Centro, Ñuñoa and Estación Central. These communes have been populated in recent years, mainly by means of huge buildings, which undoubtedly cause problems in the neighborhood, since, for example, they affect the privacy of those who live in lower heights, in addition to generating negative externalities, such as increase in noise pollution and suspended dust. This must be considered, since there is currently a requirement to apply the Strategic Environmental Assessment (SEA) in the design stage of urban regulatory plans, however, there are gaps that hinder the applicability of this tool. In this context, this article aims to analyze the difficulties around the application of the SEA in the communal regulatory plans in Chile, which gives rise to some proposals to overcome the existing obstacles. It is concluded that it is essential to citizenize the regulatory plan, on issues such as modifications to it and consideration of environmental variables in the design and monitoring phase, through the SEA Methodology. The research has a documentary design, with the use of the literature review technique and the application of critical analysis.